Manajemen Kurikulum dan Evaluasi Dalam Meningkatkan Lulusan S1 PAI di STAI Shalahuddin Al-Ayubi Jakarta - Kiswantoro Dedy; Ardani Achmad; Siti Mamduhah; Hanafiah Hanafiah (Peneliti.net, 2023)
The purpose of this research is to elaborate on curriculum management and evaluation in increasing graduates at STAI Shalahudin Al-Ayubi Jakarta. The research method used is descriptive qualitative. The results of the study show that Curriculum Management in Improving Graduate Quality consists of four stages, namely planning, organizing, implementing, and evaluating. Curriculum planning includes determining objectives, determining methods, determining material or content, and determining evaluation. Organizing the curriculum includes preparing an academic calendar, arranging schedules, setting the duties and obligations of teaching staff, and campus activity programs. Implementation of the curriculum includes learning materials or materials, learning strategies and methods, learning facilities and infrastructure, and learning assessment systems. Evaluation of the curriculum includes evaluation of educational goals, evaluation of content or materials, evaluation of learning strategies, and evaluation of assessment programs. The supporting factors are professional educators and complete infrastructure, while the inhibiting factors are the placement of available lecturers with low curriculum requirements, research and lecturer service